Electronic Word Of Mouth, Brand Trust, Dan Lifestyle Sebagai Determinan Purchase Intention Konsumen AEON Sushi Di Jabodetabek - Febry Lodwyk Rihe Riwoe; Mumuh Mulyana; Mashadi Mashadi; Siti Azzahra Suratman (Program Vokasi dan LPPM IBI Kesatuan, 2026)
This study examines the effects of electronic word of mouth (e-WOM), brand trust, and lifestyle on consumers’ purchase intention toward AEON Sushi in the Greater Jakarta area. A quantitative, cross-sectional survey was conducted among 151 respondents who lived in Greater Jakarta, were familiar with AEON Sushi, and had purchase experience or purchase consideration concerning the product. Data were collected using an online questionnaire and analyzed using partial least squares structural equation modeling (PLS-SEM) with SmartPLS 4. The results show that e-WOM positively affects purchase intention (β = 0.196; t = 2.229; p = 0.026), brand trust positively affects purchase intention (β = 0.280; t = 3.306; p = 0.001), and lifestyle has the strongest positive effect on purchase intention (β = 0.379; t = 4.608; p < 0.001). The model explains 51.3% of the variance in purchase intention (R² = 0.513), while Q²predict of 0.474 indicates predictive relevance relative to the naïve benchmark. These findings suggest that purchase intention toward AEON Sushi is shaped not only by online consumer information and confidence in the brand but also by the degree to which the product fits consumers’ urban and contemporary lifestyles. The study recommends strengthening authentic online reviews, communicating product quality and safety consistently, and positioning AEON Sushi as a convenient culinary choice that fits the lifestyle of young urban consumers. The interpretation remains subject to the limitations of non-probability sampling, respondent concentration among women and individuals aged 20–25 years, and the reduced number of retained indicators in several constructs.